PENGARUH GAYA KEPEMIMPINAN KEPALA SEKOLAH DAN SARANA PRASARANA TERHADAP KINERJA GURU SEKOLAH MENENGAH KEJURUAN (SMK) DI KABUPATEN GOWA - Hanif Aji Muslim; Hasanah Nur; Amiruddin (Program Studi S2 Pendidikan Teknologi dan Kejuruan, 2024)
The aim of this research is to determine (1) the influence of the principal's leadership and infrastructure together on teacher performance. (2) the partial influence of the principal's leadership and infrastructure on teacher performance. This type of research is explanatory research using a quantitative approach. The subjects of this research were all teachers from two schools, namely SMK Somba Opu and SMK YPKK Limbung in Gowa Regency, totaling 84 respondents using a sampling technique, namely census. The data analysis method uses descriptive analysis and multiple linear regression analysis with the help of the SPSS program. The research results show that (1) There is an influence of the principal's leadership and infrastructure together on teacher performance with an F test of 52.463. This means that the principal's leadership and infrastructure work together to create higher teacher performance. (2) There is a positive and significant influence of the principal's leadership and partial infrastructure on teacher performance. The positive and significant influence of the principal's leadership on teacher performance is proven by the t test value of 5.254. This means that the better the principal's leadership, the higher the teacher's performance. There is a positive and significant influence of infrastructure on teacher performance as evidenced by the t test value of 2.924. This means that the more complete the school infrastructure, the teacher performance will increase.